ENVIRONMENTAL INFLUENCE ON HARD ALLOY METAL RUNOUT - A. A. RYZHKIN; A. I. BOKOV; V. V. ZOTOV; D. P. GLOBA (Advanced Engineering Research)
The subject matter of this article is the result of oxygen influence on oxidative wear of the carbide tool. Based on equation of entropy balance in theoretical dependence for the calculation of wear rate, the contribution of oxidation reactions of hard alloy metal components to the general mutual of metal cut-ting entropy is considered. Twin-layer coatings influence of carbide and nitride titanium on declination of oxidative wear is represented.